The time of the tribes : the decline of individualism in mass society - Maffesoli, Michel (Theory, culture & society (Unnumbered), 1996)
Michel Maffesoli argues that the conventional approaches to understanding solidarity and society are deeply flawed. He contends that mass culture has disintegrated and that today social existence is conducted through fragmented tribal groupings, organized around the catchwords, brand-names and sound-bites of consumer culture.